Investigation on the impact of three different quaternary methyl ammonium cartridges on the radiosynthetic yields of [18F]fluoromethyl tosylate. (23rd July 2019) - Stimson, Damion H.R.; Qiao, Zheng; Reutens, David C.; Venkatachalam, Taracad K.; Bhalla, Rajiv
Abstract : Our recent investigations for the radiosynthesis of [ 18 F]fluoromethyl tosylate have highlighted that choice of quaternary methyl ammonium (QMA) cartridge used during the radiosynthesis can significantly impact the radiochemical yields. Often the details of the QMA cartridge used in fluourine‐18 syntheses are not fully described. However, our studies demonstrate that the type, the size, and nature (method by which it has been conditioned) of the QMA cartridge used during the radiosynthesis can make a significant impact in the labelling efficiency. This paper investigates the use of three QMA cartridges and demonstrates that radiochemical yield (decay corrected) of [ 18 F]fluoromethyl tosylate can increase from 46% to 60% by simply changing the QMA cartridge (and leaving all other reagents and labelling conditions exactly the same). These learnings may be applied to improve the radiochemical yields of a number of [ 18 F]‐fluorinated tracers (and synthons), where the labelling step is base‐sensitive to increase the radiochemical yield, thereby significantly benefiting the radiochemistry and nuclear medicine community. This paper also highlights the necessity of the radiochemistry community to ensure the details of QMA cartridges used in fluorine‐18 chemistry are fully and accurately described, since this will improve the translation of radiochemical methods from one laboratory to another. Abstract : Impact of 3 different QMA cartridges on the yields of [ 18 F]fluoromethyl tosylate.